2007
DOI: 10.1007/s00134-007-0584-4
|View full text |Cite
|
Sign up to set email alerts
|

Infusions of rocuronium and cisatracurium exert different effects on rat diaphragm function

Abstract: Objective: Aminosteroidal and benzylisoquinoline neuromuscular blocking agents are used in the intensive care unit to facilitate mechanical ventilation. The use of these agents has been associated with development of critical illness myopathy; however, the relative frequency of myopathy development among agents is not known. The aim of our study was to compare the effects of 24 h infusion of rocuronium or cisatracurium on the diaphragm in mechanically ventilated rats. Design: Randomized, controlled experiment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…A possible complication of using neuromuscular-blocking agents in the ICU is skeletal muscle myopathy and contractile dysfunction. In this regard, two investigations reveal that use of the neuromuscular-blocking agent rocuronium increases the magnitude of MV-induced diaphragmatic contractile dysfunction in rats (108,109). In contrast, another recent study using a porcine model of MV concluded that treatment of animals with rocuronium does not have an additive effect on MVinduced diaphragm dysfunction (78).…”
Section: Impact Of Age and Drugs On Mv-induced Diaphragmatic Contractmentioning
confidence: 99%
“…A possible complication of using neuromuscular-blocking agents in the ICU is skeletal muscle myopathy and contractile dysfunction. In this regard, two investigations reveal that use of the neuromuscular-blocking agent rocuronium increases the magnitude of MV-induced diaphragmatic contractile dysfunction in rats (108,109). In contrast, another recent study using a porcine model of MV concluded that treatment of animals with rocuronium does not have an additive effect on MVinduced diaphragm dysfunction (78).…”
Section: Impact Of Age and Drugs On Mv-induced Diaphragmatic Contractmentioning
confidence: 99%
“…Moreover, the use of steroid NMBAs and duration of infusion exceeding 48 hours seem to further favor the occurrence of myopathies. 40,41 Confirming these data, in the ACURASYS study, in which patients received a short course of nonsteroid NMBAs, 6 the incidence of ICU-acquired paresis (evaluated based on the Medical Research Council 33 score on day 28 or at the time of ICU discharge) was not higher in paralyzed patients than in the control group. Furthermore, in the meta-analysis by Alhazzani and colleagues, 25 the use of NMBAs was not associated with an increased risk of ICUAW.…”
Section: Neuromuscular Blocking Agents and Intensive Care Unit-acquirmentioning
confidence: 81%
“…42 NBDs have been defined as a risk factor for critical illness polyneuropathy and myopathy, conditions manifested by muscle weakness in critically ill patients. [11][12][13][14]42 Moreover, infusion of rocuronium 12 and cisatracurium 14 for a single day in rats compromises diaphragmatic function by a myopathic mechanism that does not involve neuromuscular transmission failure. 12 Moreover, the combination of 18 to 69 hours of complete diaphragmatic inactivity and mechanical ventilation results in marked atrophy of myofibers in the diaphragm of humans.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Moreover, long-term administration of NBDs is a risk factor for the development of critical illness polyneuropathy. [11][12][13][14] Finally, recent animal data suggest that a constant neuromuscular blockade with rocuronium and cisatracurium over only a single day evokes a myopathy that significantly decreases diaphragmatic force. 12,14 Therefore, we feel it is important for clinicians to get information about variables that predict the duration of action of NBDs administered long-term.…”
mentioning
confidence: 99%
See 1 more Smart Citation